Prevalence and prognosis of hyperdynamic left ventricular systolic function in septic patients: a systematic review and meta-analysis - Ryota Sato; Filippo Sanfilippo; Daisuke Hasegawa; Narut Prasitlumkum; Abhijit Duggal; Siddharth Dugar (Annals of Intensive Care, 2024)
Abstract Purpose The prevalence of hyperdynamic left ventricular (LV) systolic function in septic patients and its impact on mortality remain controversial. In this systematic review and meta-analysis, we investigated the prevalence and association of hyperdynamic LV systolic function with mortality in patients with sepsis. Methods We searched MEDLINE, Cochrane Central Register of Controlled Trials, and Embase. Primary outcomes were the prevalence of hyperdynamic LV systolic function in adult septic patients and the associated short-term mortality as compared to normal LV systolic function. Hyperdynamic LV systolic function was defined using LV ejection fraction (LVEF) of 70% as cutoff. Secondary outcomes were heart rate, LV end-diastolic diameter (LVEDD), and E/e’ ratio. Results Four studies were included, and the pooled prevalence of hyperdynamic LV systolic function was 18.2% ([95% confidence interval (CI) 12.5, 25.8]; I 2  = 7.0%, P < 0.0001). Hyperdynamic LV systolic function was associated with higher mortality: odds ratio of 2.37 [95%CI 1.47, 3.80]; I 2  = 79%, P < 0.01. No difference was found in E/e’ (P = 0.43) between normal and hyperdynamic LV systolic function, while higher values of heart rate (mean difference: 6.14 beats/min [95%CI 3.59, 8.69]; I 2  = 51%, P < 0.0001) and LVEDD (mean difference: − 0.21 cm [95%CI − 0.33, − 0.09]; I 2  = 73%, P < 0.001) were detected in patients with hyperdynamic LV systolic function. Conclusion The prevalence of hyperdynamic LV systolic function is not negligible in septic patients. Such a finding is associated with significantly higher short-term mortality as compared to normal LV systolic function.